Pengaruh Daya Tarik Wisata Kuliner Terhadap Kepuasan Wisatawan di Pasar Lama Tangerang - Septiani, Dinda Dwi; Nofiyanti, Fifi; Halik, Nawawi (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2100, 2026)
This study aims to examine the influence of culinary tourism attraction on visitor satisfaction at Pasar Lama Tangerang. A quantitative approach with an associative research design was employed. The study population consisted of visitors who had visited Pasar Lama Tangerang, with a sample of 100 respondents selected using the Slovin formula and a probability sampling technique through simple random sampling. Data were collected through questionnaires, observations, and interviews. The culinary tourism attraction variable was measured using four dimensions: product, price, packaging, and assurance, while visitor satisfaction was measured through product quality, price, service quality, and convenience. Data analysis was conducted using SPSS Statistics version 27, including validity and reliability tests, descriptive analysis, simple linear regression, correlation coefficient, coefficient of determination, and partial (t-test) analysis. The results indicated that partial test revealed that culinary tourism attraction had a positive and significant effect on visitor satisfaction. It can be concluded that improving culinary tourism attractions leads to higher visitor satisfaction. Therefore, destination managers and culinary business operators are encouraged to continuously enhance product quality, maintain food hygiene, improve service quality, and develop innovative culinary offerings to increase visitor satisfaction and encourage repeat visits. Keywords: culinary tourism attraction, visitor satisfaction, culinary tourism